Aktivitas Penangkapan Radikal Bebas dari Infus Kelopak Bunga Rosella yang Difermentasi dengan Lactobacillus - Sartini, .; Lethe, Christiana; Frengky, . (Jurnal Farmasi Indonesia, 2014)
The research aimed to investigate the free radical scavenging activity of ethyl acetate fraction of roselle calyces infusion fermented by Lactobacillus casei strain Shirota against free radical agent, DPPH (2,2-di-phenyl-2-picrylhydrazyl). In sequence, the roselle calyces were extracted by infusion method with concentration at 5% w/v. The infusion was fermented using Lactobacillus casei strain Shirota during 3x24 hours at 37â°C. As regard the fermentation process, the result of that was extracted using ethyl acetate. Free radical scavenging activity was measured using DPPH method with unfermented-ethyl acetate fraction as control negative. As the result, both fermented and unfermented-ethyl acetate fraction exhibited free radical scavenging activity at 370.68 ppm and 685.49 ppm, respectively. These results suggest that antioxidant activity of fermented-ethyl acetate fraction could be 1.85 greater than unfermented-ethyl acetate fraction of roselle calyces infusionKeywords : Hibiscus sabdariffa L., Lactobacillus casei Shirota strain, free radical scavenging, DPPH